2019
DOI: 10.1002/jor.24349
|View full text |Cite
|
Sign up to set email alerts
|

Wrapping With Basic Fibroblast Growth Factor‐Impregnated Collagen Sheet Reduces Rat Sciatic Nerve Allodynia

Abstract: Autologous vein wrapping is used to treat recurrent chronic constriction neuropathy and traumatic peripheral nerve injury. However, its use is restricted due to the inability to obtain sufficiently long veins for larger grafts. We previously reported that vein‐derived basic fibroblast growth factor (bFGF) promotes heme oxygenase‐1 (HO‐1), which reduces allodynia via its anti‐inflammatory properties. To mimic vein wrapping, we developed a collagen sheet impregnated with bFGF. Chronic constriction injury (CCI) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Here, frozen vein contained a higher amount of bFGF than sciatic nerve. We previously reported that bFGF stimulated rat sciatic nerve in vitro and that bFGF-absorbed collagen sheet wrapping promoted Hmox1 expression and improved mechanical allodynia [23]. Our present observation suggests that ECM-derived bFGF in vein may induce Hmox1 expression.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Here, frozen vein contained a higher amount of bFGF than sciatic nerve. We previously reported that bFGF stimulated rat sciatic nerve in vitro and that bFGF-absorbed collagen sheet wrapping promoted Hmox1 expression and improved mechanical allodynia [23]. Our present observation suggests that ECM-derived bFGF in vein may induce Hmox1 expression.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies proposed the mechanism that autologous vein wrapping exerted its therapeutic effect through vein-derived trophic factors [9,10,23]. We previously reported that Hmox1 following fresh VW and recombinant bFGF stimulate Hmox1 expression in sciatic nerve cells in vitro [9].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rats ( n = 5 per group) were subjected to the von Frey test according to our previous report [ 9 – 11 , 24 ] on postoperative days (PODs) 1, 3, 5, 7, and 14. Following randomization and 1-h acclimation to the test cage, the von Frey test was conducted by applying six von Frey filaments (3.922 mN, 5.882 mN, 9.804 mN, 13.725 mN, 19.608 mN, 39.216 mN) (Mono-filament Kit; Smith & Nephew, Germantown, WI) to the hind paw perpendicular to the plantar surface.…”
Section: Methodsmentioning
confidence: 99%
“…Dysesthesia involves a disagreeable sensation such as a painful burning, prickling or aching feeling, and allodynia is defined as an unpleasant sensation that occurs with light touch. Sciatic nerve injury (SNI) is more closely related to allodynia than to dysesthesia ( Mukai et al, 2019 ). Patients with neuropathic pain after SNI have suffered from poor quality of life due to anxiety, depression and severe pain ( Bernetti et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%